„Gdzie ci mężczyźni prawdziwi tacy”, czyli o językowo-kulturowym obrazie profesjonalisty w reklamie - Pomianek, Aneta (Słowo. Studia językoznawcze, 2010)
The main topic of the article is to discuss linguistic and cultural picture of professional the in advertisement. The research material is based on screened on Polish television from 2005 to 2007. The status of a lexeme a man in modern Polish is analysed. Then the description of a male in a commercial is searched. Having analyzed the research material the author differentiates two types of a professional man on the basis of the age. There are both a young and an old man whose picture is created on the stereotype patterns. One of the most important elements in such descriptions is the appearance. The professional controls over the modernity, tradition, worldliness, progressiveness, independence, intense life, scholarship, aspirations, aesthetic look, perfection in action, overcoming difficulties, education, need of luxury, sense of one’s value and the strength of character.